Random processes of interaction between track and rolling stock - A. Y. Kogan; E. D. Zagitov; I. V. Poleschyuk (Вестник Научно-исследовательского института железнодорожного транспорта)
Optimization of life-cycle cost of structures of railway track for different lines is a multi-task. Railway track can be seen as a dynamic system, which is got as the input deteriorating impact - operational load and enhancing impact - maintenance and repair activities. Results of these two effects on physical level are the force indicators of interaction between track and rolling stock and parameters depend on them, which include: forces of interaction in contact point of wheel - rail system; deformations and stresses of elements of track superstructure and in the main level of subgrade; track wear, accumulation of residual deformations in track and its elements. It is known that the actual axial loads on carriage, geometry of the track, irregularities on rolling surface of the wheels and other parameters are random. To analyze the interaction between track and rolling stock in the conditions of the random nature of disturbances methods of the probability theory and the theory of random functions should apply as the input of the system. This article presents the structure and the basic expression patterns of interaction model between track and rolling stock, developed on the basis of methods of the theory of random functions and probability theory. A comparison of results of calculations of interaction between track and rolling stock was made on the basis of stochastic model by calculations of “Universal Mechanism” model and NUCARS. Stochastic methods, the main provisions of which are outlined in this article, make it possible to determine the probability characteristics of the stress-deformation state of the elements of track superstructure and the stresses on the main level of the subgrade with the real flow of operational loads on a given area. This method also helps solving the most important technical and economic problems related to the operation of track infrastructure.